A Modified CQ Algorithm for Solving the Multiple-Sets Split Feasibility Problem and the Fixed Point Problem for Nonexpansive Mappings: Suparat Kesornprom, Nattawut Pholasa, Prasit Cholamjiak - Team, Support (Thai Journal of Mathematics, 2019)
In this work, we propose a new relaxed CQ algorithm for solving the multiple-sets split feasibility problem (MSFP) and the fixed point problem for nonexpansive mappings. We obtain weak and strong convergence theorems of the proposed algorithm in Hilbert spaces. Finally, we provide numerical experiments to show the efficiency of our algorithm.